Utilização de persulfato de sódio para tratamento de água subterrânea contaminada por mistura de diesel e biodiesel - Adrielly Fonseca Fialho Ferreira (2019)
Soil and groundwater contamination by petroleum products and its hazardous constituents, BTEX and PAH, has increased in the past decades. As a consequence, more studies aiming at the development of remediation techniques of these matrices must be carried out. Among the techniques applied for the remediation of these sites, we highlight Chemical Oxidation in situ (ISCO). The objective of this study was to evaluate the performance of ISCO, using sodium persulfate as an oxidant, on the remediation of water contaminated by the diesel / biodiesel mixture, in a ratio of 10% of biodiesel (B10) added to S10 diesel. In order to achieve this goal, this work was divided in two stages. In the first stage, the solubility of different substances mixed in biodiesel with diesel S10 and S500 in water was evaluated. Among the mixtures analyzed, B100 (100% biodiesel) and B10 showed higher solubility. BTEX concentrations were higher than the values recommended by Ordinance 2914/11 in the aqueous phase of this mixture, thus confirming the need for the oxidative treatment of the aqueous phase. The second stage of this work was performed in three steps and consisted of evaluating the use of sodium persulfate as an oxidant in the treatment of water contaminated by the B10 mixture in the presence of an iron rich soil (latosol). At first, the interaction between different concentrations of PS and organic matter (OM) present in the soil was evaluated. Results showed an average oxidant consumption of 1.2 g of persulfate for all concentrations. The second phase consisted in the evaluation of different concentrations of PS in the treatment of distilled water contaminated by the B10 mixture. In the systems containing latosol, 41%, 35% and 29% removal of dissolved organic carbon (COD) were achieved for concentrations of 5, 10 and 20 g L-1 of persulfate, respectively. BTEX compounds were fully removed for all concentrations of PS used. However, benzene was formed and accumulated in the system when of 5 g L-1 of persulfate was used. The third phase evaluated the use of the 5 g L -1 of persulfate in the presence of soil with the addition of FeSO4 in order to evaluate the action of dissolved iron as a catalyst in the treatment of groundwater contaminated by the B10 mixture. Results showed that the addition of the metal salt did not increase COD removal. It is possible that carbonate radical species were formed in the system due to the physicochemical properties of groundwater. No significant changes were observed in the chemical or in the physical properties of the latosol after treatment.